Electrochemical immunosensor for multiplexed detection of food-borne pathogens using nanocrystal bioconjugates and MWCNT screen-printed electrode - Viswanathan, Subramanian (2012)
Bacterial food poisoning is an ever-present threat that can be prevented with proper care and handling of food products. A disposable electrochemical immunosensor for the simultaneous measurements of common food pathogenic bacteria namely Escherichia coli O157:H7 (E. coli), campylobacter and salmonella were developed. The immunosensor was fabricated by immobilizing the mixture of anti-E. coli, anticampylobacter and anti-salmonella antibodies with a ratio of 1:1:1 on the surface of the multiwall carbon nanotube-polyallylamine modified screen printed electrode (MWCNT-PAH/SPE). Bacteria suspension became attached to the immobilized antibodies when the immunosensor was incubated in liquid samples. The sandwich immunoassay was performed with three antibodies conjugated with specific nanocrystal ( -E. coli-CdS, -campylobacter-PbS and -salmonella-CuS) which has releasable metal ions for electrochemical measurements. The square wave anodic stripping voltammetry (SWASV) was employed to measure released metal ions from bound antibody nanocrystal conjugates. The calibration curves for three selected bacteria were found in the range of 1 × 103 – 5 × 105 cells mL−1 with the limit of detection (LOD) 400 cells mL−1 for salmonella, 400 cells mL−1 for campylobacter and 800 cells mL−1 for E. coli. The precision and sensitivity of this method show the feasibility of multiplexed determination of bacteria in milk samples.